2004
DOI: 10.1089/jwh.2004.13.898
|View full text |Cite
|
Sign up to set email alerts
|

Hidden Victims: The Healthcare Needs and Experiences of Older Women in Abusive Relationships

Abstract: Older women victims have difficulty initiating discussions about IPV with their providers. Providers are encouraged to identify signals of potential abuse and to create privacy with all patients to discuss difficult issues, such as IPV, and to be knowledgeable about appropriate referrals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
89
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(93 citation statements)
references
References 23 publications
2
89
0
2
Order By: Relevance
“…A main focus is the development of large prospective studies to delineate the long-term course of abuse on women's lives and mulitfactorial randomized controlled trials of ''best practice'' interventions (Cohn, Salmon, & Stobo, 2002;Nelson, Nygren, McInerney, & Klein, 2004;Wathen & MacMillan, 2003). As a starting point, clinicians might routinely assess partner violence using questions from the WEB Scale and the BRFSS, or other measurement tools (Bonomi, Allen, et al, 2006), and ensure a comprehensive and compassionate response to women who report abuse in their relationships (Zink et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A main focus is the development of large prospective studies to delineate the long-term course of abuse on women's lives and mulitfactorial randomized controlled trials of ''best practice'' interventions (Cohn, Salmon, & Stobo, 2002;Nelson, Nygren, McInerney, & Klein, 2004;Wathen & MacMillan, 2003). As a starting point, clinicians might routinely assess partner violence using questions from the WEB Scale and the BRFSS, or other measurement tools (Bonomi, Allen, et al, 2006), and ensure a comprehensive and compassionate response to women who report abuse in their relationships (Zink et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The broad definition of partner violence proposed by the CDC is necessary in order to adequately characterize all forms of violence and abuse that could harm victims involved with abusive intimate partners. The growing focus on partner violence in women older than 65 years of age is of particular importance, given the potential for social isolation and functional and cognitive impairment in older women (Cohen, Forte, Du Mont, Hyman, & Romans, 2005) and the tendency for health care providers to think of partner violence as a problem of younger women (Lachs, 2004;Zink, Jacobson, Regan, & Pabst, 2004).…”
mentioning
confidence: 99%
“…However, initiatives require agencies and individuals to recognise the issues surrounding domestic abuse and older women before they can be effective. This is echoed by Zink et al (2004Zink et al ( , 2005 who highlight that healthcare providers need to be alert to domestic abuse as an issue for older women in consultations as older women are often reluctant to disclose this type of information. They highlight that in addition to the reasons for non-disclosure identified with younger women, they are further compounded with older women through generational factors such as notions of privacy surrounding the home and intimate relationships.…”
Section: Potential Barriers To Older Women Reporting Domestic Abusementioning
confidence: 99%
“…Similar to the women in our sample, the women in the USA also value medical proof, such as photographs of injuries taken by HCPs, that helps them establish credible testimony against their perpetrators in a court of law (Dienemann, Glass & Hyman, 2005). Another study conducted in the USA indicated that battered women also value information from HCPs on community resources, such as IPV programs (Zink, Jacobson, Regan & Pabst, 2004). Like other studies, our study shows that beneficial assistance from HCPs ultimately helps women to make decisions that are right for them in an effort to break the cycle of violence.…”
Section: Discussionmentioning
confidence: 61%